LATERAL THINKING: 2-D INTERPRETATION OF THERMOCHRONOLOGY IN CONVERGENT OROGENIC SETTINGS - Batt G.E.; Brandon M.T. (My University, 2002)
Lateral motion of material relative to the regional thermal and kinematic frameworks is important in the interpretation of thermochronology in convergent orogens. Although cooling ages in denuded settings are commonly linked to exhumation, such data are not related to instantaneous behavior but rather to an integration of the exhumation rates experienced between the thermochronological 'closure' at depth and subsequent exposure at the surface. The short spatial wavelength variation of thermal structure and denudation rate typical of orogenic regions thus renders thermochronometers sensitive to lateral motion during exhumation. The significance of this lateral motion varies in proportion with closure temperature, which controls the depth at which isotopic closure occurs, and hence, the range of time and length scales over which such data integrate sample histories. Different chronometers thus vary in the fundamental aspects of the orogenic character to which they are sensitive. Isotopic systems with high closure temperature are more sensitive to exhumation paths and the variation in denudation and thermal structure across a region, while those of lower closure temperature constrain shorter-term behaviour and more local conditions.Discounting lateral motion through an orogenic region and interpreting cooling ages purely in terms of vertical exhumation can produce ambiguous results because variation in the cooling rate can result from either change in kinematics over time or the translation of samples through spatially varying conditions. Resolving this ambiguity requires explicit consideration of the physical and thermal framework experienced by samples during their exhumation. This can be best achieved through numerical simulations coupling kinematic deformation to thermal evolution. Such an approach allows the thermochronological implications of different kinematic scenarios to be tested, and thus provides an important means of assessing the contribution of lateral motion to orogenic evolution.
Keywords: LATERAL MOTION; THERMOCHRONOLOGY; OROGENIC REGIONS